Protein-rich and cholesterol-free crackers from green mungbean (Phaseolus aureus) - Nicdao, Bernadette Marie Oloroso (College of Home Economics, University of the Philippines Diliman, 2012)
With high prices of commodity, no doubt that protein-energy malnutrition still remains to be one of the nutritional problems in the Philippines. Legume seeds are the alternative in providing protein in the diet. Protein supplementation is best done on crackers since they are quick, ready-to-go foods. The study aims to develop a protein-rich and cholesterol-free cracker made from green mungbean that is acceptable to young consumers by determining the optimum level of mungbean to flour ration, evaluating the consumer acceptance and determining the physico-chemical properties. Crackers were made from powderized green mungbean, all purpose flour, salt, baking soda, baking powder, palm oil and water. Mungbean was substituted for flour at 0, 9, 18 and 27%. A total of 60 individuals in two sessions, participated in the consumer acceptance test. Attributes evaluated were appearance, crispness, flavor, aftertaste and overall acceptance. Crispness was the only attribute that resulted in a significant difference (α=0.05) amongst treatments. With an Hedonic scale set at 5.5, regression analysis showed that mungbean concentrations from 17% and above is predicted to give crackers that are acceptable to consumers. Proximate analyses showed that the control and crackers with 18% mungbean had similar moisture content and water activity. Crackers with 18% mungbean had significantly higher protein content than the control, the former being able to meet the standards of Codex Alimentarius for claim on protein-rich for all age groups except for males (16-18 years old). All ingredients were plant based, thus mungbean cracker is also cholesterol-free.